A atuação do tutor presencial no curso de pedagogia UAB/UFSM e sua relação com os processos de aprendizagem - Soeiro, Aline Fernanda (2019)
This research, developed under the Professional Master Program in Public Policy and Educational Management of the Federal University of Santa Maria - UFSM, in the research line “Policies and Management of Higher Education- LP1”, from 2017 to 2019, focused on understanding the possible implications of the tutor's performance in the teaching-learning process of students, considering the scope of poles of the Education Course distance UFSM under the Brazilian Open University (UAB). Initially, the systematization of legal norms was performed, trying to understand the main attributions of the present tutor, and how they have been developed in the UAB/UFSM Pedagogy Course.We also seek to understand, from the point of view of the research subjects how the attributions of these tutors can influence the teaching-learning processes of students.The applied research was based on a qualitative approach, combining consultation with empirical documents and empirical data, listening to the subjects directly involved with the course: present tutors and students with active enrollment. Data collection involved semi-structured interviews with present tutors, who developed their tutoring activities longer in the course.In addition, it was used to collect the data a dialogical listening with students from two poles of the UAB/UFSM Pedagogy Course. To understand and compile the data, we opted for the Discursive Textual Analysis, which emerged three categories: perception of the subjects about the activities developed by the present tutor; relations/interactions between the subjects involved in the teaching-learning processes in distance learning, and the influence of the present tutor in the teaching-learning processes. After, carefully analyzing each of these categories, in light of the questions and objectives of the study, it can be concluded that the work of the present tutor makes a difference in the academic life of the students, and that this provides a differential in the teaching-learning processes, and is directly linked to human relationships and motivational encouragement. Thus, was proposed, as a final product, to use the electronic tool “Padlet”, which is a collaborative learning environment, as it is understood that this can be a way of qualifying the performance of the tutors of the UAB/UFSM Pedagogy course, with exchanges of experiences, minimizing the weaknesses pointed out during this research.